CFM56-7B Electronic Engine Control System Performance During Ground Run-Up Test - Ani Widuri; Sovian Aritonang; Gita Amperiawan; Andy Marjono Putranto; Lalu Aan Sasaka Akbar; Novan Risnawan (Institut Teknologi Dirgantara Adisutjipto, 2026)
The performance of the Electronic Engine Control (EEC) system is essential for ensuring safe aircraft operation following engine maintenance. This study evaluates the EEC performance of a CFM56-7B turbofan engine during an on-aircraft Engine Ground Run-Up (EGR) test conducted after engine replacement on a Boeing 737-800 Next Generation aircraft. The test was performed under controlled ground conditions in accordance with the Aircraft Maintenance Manual, and key EEC-controlled parameters—including fan speed (N1), compressor speed (N2), exhaust gas temperature (EGT), fuel flow, lubrication parameters, and engine vibration—were recorded using the aircraft’s built-in sensor system. The results indicate that all monitored parameters remained within manufacturer-specified acceptance limits during engine start, idle, Maximum Power Assurance, and static take-off power conditions, demonstrating stable EEC regulation under both transient and steady-state operation. Fuel consumption during the EGR procedure was consistent with the applied power settings, reflecting appropriate fuel scheduling. Comparison with representative test-cell–based studies show similar performance trends, with expected differences in thermal behavior attributable to on-wing installation effects during ground operation. Overall, the findings confirm that on-aircraft EGR testing provides an effective and operationally representative approach for post-maintenance validation of EEC performance, bridging the gap between test-cell evaluations and actual aircraft operation.